1) ab - ac + yb - yc = a * (b-c) + y * (b-c) = (b-c) * (a+y)
2) 3x + 3y - bx - by = 3 (x+y) - b * (x+y) = (x+y) * (3-b)
3) 4n - nc - 4 + c = n * (4-c) - (4-c) = (4-c) * (n-1)
4) x⁷ + x³ - 4x⁴ - 4 = x³ * (x⁴ + 1) - 4 (x⁴ + 1) = (x⁴ + 1) * (x³ - 4)
5) 6mn - 3m + 2n - 1 = 3m * (2n-1) + 2n - 1 = (2n-1) * (3m+1)
6) 4a⁴ - 5a³y - 8a + 10y = a³ * (4a-5y) -2 (4a-5y) = (4a-5y) * (a³ -2)
7) a²b² - a + ab² - 1 = a * (ab² - 1) + ab² - 1 = (ab²-1) * (a+1)
8) xa - xb² - ya + zb² - za + yb² = a * (x-y-z) - b² * (x-z-y) = (x-y-z) * (a-b²)